Предмет: Алгебра,
автор: bnika1496
Решите уравнение. Пожалуйста
Приложения:
Ответы
Автор ответа:
0
Объяснение:
(√(cos²x-cosx))/sinx-1=0
(√(cos²x-cosx))/sinx=1
√(cos²x-cosx)=sinx
cos²x-cosx=sin²x
cos²x-cosx=1-cos²x
cos²x-cosx-1+cos²x=0
2cos²x-cosx-1=0
t=cosx
2t²-t-1=0
t1=-1/2, t2=1 => cosx=-1/2 или cosx=1
...
cosx=-1/2
x=arccos(-1/2) или 2π-x=arccos(-1/2)
x=2π/3+2nπ, n€Z 2π-x=2π/3+2nπ, n€Z
x=4π/3+2nπ, n€Z
...
cosx=1
x=2nπ, n€Z
...
x=2π/3+2nπ, n€Z
x=4π/3+2nπ, n€Z
x=2nπ, n€Z
Объединение: x=2π/3+2nπ, n€Z
x=4π/3+2nπ, n€Z
vlad97ua:
Странно, что не учтено ОДЗ...
Похожие вопросы
Предмет: Русский язык,
автор: dilyasi
Предмет: Русский язык,
автор: Bexa12091999
Предмет: Русский язык,
автор: Nuriza97
Предмет: Русский язык,
автор: 18aprela2005
Предмет: Алгебра,
автор: Fluffy0807